An investigation on the occurrence of stable cage whirl motions in ball bearings based on dynamic simulations. (November 2016) - Niu, Linkai; Cao, Hongrui; He, Zhengjia; Li, Yamin
Abstract: The occurrence of stable cage whirl in ball bearings with outer ring guided cage under solid lubrication conditions is investigated based on dynamic simulations. The roles of the cage forces in stable whirls and the ball spacing characteristics under stable and unstable conditions are investigated. Results show that the stable whirl motion significantly depends on the ball-cage pocket contact force and the cage-guiding ring forces. Unequal ball spacing is important to the increase of the whirl radius for stable whirl. Furthermore, the ball cannot drive the cage continuously under severe skidding conditions, and thus increase the cage instability. Highlights: Forces to hold constant whirl radius and speed are studied by dynamic simulations. The constant whirl radius significantly depends on the ball-cage pocket contact force. Ball-cage pocket contact force is the main driving force for a cage to whirl ahead. Unequal ball spacing is an important characteristic for stable whirl. Cage instability occurs under severe skidding conditions.